2010
DOI: 10.1016/s0027-9684(15)30772-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV Knowledge and Its Contribution to Sexual Health Behaviors of Low-Income African American Adolescents

Abstract: Objectives Although many factors contribute to racial disparities in HIV/AIDS among young African Americans, knowledge is a particularly modifiable factor. However, little information has been published about the current HIV knowledge of African American teens or to what extent knowledge independently contributes to their sexual behavior and health. This study aimed to describe the level of knowledge among this at-risk population and determine whether knowledge contributes to variance in sexual behavior and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 48 publications
10
79
1
2
Order By: Relevance
“…This is consistent with previous studies regarding HIV knowledge and preventive practices among adolescents (11,12,15). Additionally, we found that the HIV knowledge of the majority (51%) of the adolescents was poor.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies regarding HIV knowledge and preventive practices among adolescents (11,12,15). Additionally, we found that the HIV knowledge of the majority (51%) of the adolescents was poor.…”
Section: Discussionsupporting
confidence: 93%
“…Many behavior theorists posit that a person must have knowledge about a disease and how to prevent the disease in order to engage in prevention behaviors (2)(3)(4)(5)(6)(7)(8)(9)(10). Studies from multiple countries other than Nigeria have assessed the relationship between HIV knowledge and sexual behavior in adolescents (11)(12)(13)(14)(15). Researchers found that higher HIV knowledge was associated with increased HIV testing, consistent condom use, delayed first sexual intercourse, and a reduced number of sexual partners (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…85,86 It was unexpected to find that participants who scored higher on the HIV knowledge quiz had more unprotected sex with older partners than participants with lower scores; a study of African American low-income adolescents also found that greater HIV knowledge was associated with more unprotected sex, although partner age differences were not examined. 87 It is also possible that greater HIV knowledge is a result of higher levels of unprotected sex. Future research should explore these unexpected interactions and ascertain whether there are other factors impacting these results.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to ascertain the reasons for the low comprehensive knowledge of HIV among adolescents in Nigeria; we do know from previous research that because adolescents and young persons have limited knowledge about the disease 30 and they are often ignorant about their vulnerabilities and levels of risk 34 , they are more likely to convey contradictory messages about HIV transmission 35 especially as peer influences increase during late adolescence and early adulthood [36][37][38][39][40] . Sexual experience, lower uptake of STI/HIV testing and less condom use which have been linked with lower knowledge of HIV among low-income African American adolescents 41 could also be the underlying factors responsible for the insufficiency in comprehensive knowledge of HIV among adolescents in Nigeria. Lack of accurate knowledge about HIV/AIDS among youth has also been linked with a dearth of comprehensive sexuality and HIV education coupled with likely inaccuracies in abstinence-only curricula used by some school systems 42 .…”
Section: Crr= Crude Rrmentioning
confidence: 99%